Castration Chemical Sanction Policy for Perpetrators of Sexual Violence Against Children of the Study of Criminal Law Politics - Krismiyarsi, Krismiyarsi (Law Research Review Quarterly, 2018)
Article 28 B paragraph (2) of the Constitution of the Republic of Indonesia confirms that the State guarantees the right of children to survival, growth and development as well as protection from violence and discrimination. Along with the rapid flow of globalization and the negative impact of the development of information technology and telecommunications, sexual violence against children is increasing. The Indonesian Child Protection Commission (KPAI), said that in 2015 there were 218 cases, in 2016 there were 120 cases, and in 2017 there were 116 cases. To address the phenomenon of sexual violence against children, the President of Indonesia issued Government Regulation in Lieu of Law No. 17 of 2016, which was subsequently upgraded to become Law, namely Law No. 17 of 2016 concerning Establishment of Government Regulation in Lieu of Law No. 1 of 2016 concerning the second amendment to Law No. 23 of 2002 concerning Child Protection becomes a law. The contents of criminal charges against perpetrators of sexual violence against children, can be subject to additional crimes in the form of announcements of the identity of the perpetrators, and can be subjected to actions in the form of chemical castration accompanied by rehabilitation and installation of electronic detection devices. The basis for considering the issuance of this Perppu minimizes sexual crimes, gives a deterrent effect for sexual offenders and prevents the intention of everyone to commit sexual crimes.